2023
DOI: 10.1186/s12978-023-01625-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge level and access barriers related to sexual and reproductive health information among youth with disabilities in China: a cross-sectional study

Abstract: Background Youth with disabilities have the same right to sexual and reproductive health (SRH) as their peers without disabilities. However, their needs and rights are often ignored. Little is known about the knowledge, needs and access barriers related to SRH information among youth with different types of disabilities in China. Methods A cross-sectional survey was carried out among 473 unmarried youth aged 15–24 with visual, hearing, physical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Consistent with previous studies in Ghana [ 23 ] and China [ 59 ], visually impaired persons were more aware and knowledgeable about SRH, including STIs and HIV/AIDS, than persons with other types of disability. Badu et al [ 34 ] also reported that visually impaired women were active seekers of SRH information.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies in Ghana [ 23 ] and China [ 59 ], visually impaired persons were more aware and knowledgeable about SRH, including STIs and HIV/AIDS, than persons with other types of disability. Badu et al [ 34 ] also reported that visually impaired women were active seekers of SRH information.…”
Section: Discussionsupporting
confidence: 89%
“…This study finding on the association between type of disability and knowledge of SRH such as STIs and HIV/AIDS is also supported by a previous study among young PwDs in Ethiopia [ 56 ]. A possible explanation for this finding is that other disabilities, such as hearing impairment, face more challenges accessing SRH information than those with visual impairment mainly due to difficulties in verbal communication and comprehension from reading [ 59 ]. The qualitative data also revealed that most visually impaired PwDs actively sought SRH information from the radio.…”
Section: Discussionmentioning
confidence: 99%
“…In many cultural contexts, including China, sexuality and reproduction are essential but often taboo topics for open discussion. People's knowledge about sexuality and reproduction is generally fragmented and incomplete(Chen et al, 2020;Guan, 2021;Qi et al, 2023). The dissemination of hearsay and scattered information, such as beliefs that 'blocked fallopian tubes result from a woman's promiscuous lifestyle' or 'children born through ART are artificial and often have problems', has contributed to the unjust stigmatization towards women.…”
mentioning
confidence: 99%